2022
DOI: 10.3390/ijms23115952
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative Effects of the Aptamer d(GGGT)4 and Its Analogues with an Abasic-Site Mimic Loop on Different Cancer Cells

Abstract: In this paper, we study the T30923 antiproliferative potential and the contribution of its loop residues in six different human cancer cell lines by preparing five T30923 variants using the single residue replacement approach of loop thymidine with an abasic site mimic (S). G-rich oligonucleotides (GRO) show interesting anticancer properties because of their capability to adopt G-quadruplex structures (G4s), such as the G4 HIV-1 integrase inhibitor T30923. Considering the multi-targeted effects of G4-aptamers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
1
0
0
Order By: Relevance
“…Concerning TBAG3, it should be noted that it folds in a parallel G4-structure with three G-tetrads and three propeller loops, which is very similar to that adopted by other antiproliferative G-quadruplexes [ 25 , 26 ]. It is well known that TBA is highly susceptible to nucleases being degraded in a few hours [ 27 ], as also reported by us ( Figure S3 ) [ 27 ]. Outcomes concerning the nuclease stability assay have indicated that all TBA derivatives significantly degrade in 72 h in serum, except TBAG4, which preserves its structure up to 72 h. It is interesting to note that there is a rough correlation between the degradability order (TBA < TBAG3 < TBAG41S ≤ TBAG4GS) and the antiproliferative activities in MDAMB 231 cells at 72 h (TBA < TBAG3 < TBAG4GS ≤ TBAG41S).…”
Section: Discussionsupporting
confidence: 81%
“…Concerning TBAG3, it should be noted that it folds in a parallel G4-structure with three G-tetrads and three propeller loops, which is very similar to that adopted by other antiproliferative G-quadruplexes [ 25 , 26 ]. It is well known that TBA is highly susceptible to nucleases being degraded in a few hours [ 27 ], as also reported by us ( Figure S3 ) [ 27 ]. Outcomes concerning the nuclease stability assay have indicated that all TBA derivatives significantly degrade in 72 h in serum, except TBAG4, which preserves its structure up to 72 h. It is interesting to note that there is a rough correlation between the degradability order (TBA < TBAG3 < TBAG41S ≤ TBAG4GS) and the antiproliferative activities in MDAMB 231 cells at 72 h (TBA < TBAG3 < TBAG4GS ≤ TBAG41S).…”
Section: Discussionsupporting
confidence: 81%
“…Aptamers, synthetic oligonucleotides, can be antiproliferative agents with benefits including size, flexibility, rapid production, stability, and low immunogenicity ( 20 ). Cytostatic G-quadruplex (GQ) oligonucleotides have been effective on glioma cell cultures ( 21 ), showing promise in this context ( 22 , 23 ).…”
Section: Introductionmentioning
confidence: 99%
“…Aptamers, synthetic oligonucleotides, can be antiproliferative agents with benefits including size, flexibility, rapid production, stability, and low immunogenicity (20). Cytostatic G-quadruplex (GQ) oligonucleotides have been effective on glioma cell cultures (21), showing promise in this context (22,23).…”
Section: Introductionmentioning
confidence: 99%